HPV distribution in cervical cancer in Portugal. A retrospective study from 1928 to 2005 - Félix, A. (2018)
Objectives To determine human papillomavirus (HPV) types in invasive cervical cancer in Portugal. Methods Cases diagnosed at the Instituto Português de Oncologia de Lisboa de Francisco Gentil from the year 1928 to 2005 were selected for HPV DNA detection and genotyping using SPF10/DEIA/LiPA25 system. Results Of the 1214 samples that were considered appropriate for HPV detection, 714 (58.8%; 95% CI: 56.0–61.6%) were positive for HPV DNA. This detection rate varied being lower in the first 3 decades (31.3%; 50.1%; 46.5%) and higher in the last decades (77.4–95.1%). This difference was due probably to the fixative used in the first three decades. The five most common types identified among HPV positive cases were HPV16 (58.2%), HPV18 (9.2%), HPV33 (6.2%), HPV45 (4.7%) and HPV31 (4.4%). Multiple infections were detected in 2.8% of the cases. HPV16 and 18 accounted for 67.4% of infections. There were no statistically significant changes of these types over the studied period. An increase at patient׳s age at diagnosis was observed in the last decades (p